Enhancing Vision-Based Navigation of Nutonomous Guided Vehicles Through Deep Learning and Cloud Integration - MEDJALDI , Amar; KARKAR , Nora Supervision; Yacine , Slimani Co-Supervision (Setif 1 University - Ferhat ABBAS , Faculty of Technology, 2026)
This work integrates cloud-based computer vision and deep learning in order to enhance the navigation of autonomous guided vehicles (AGVs). It allows the ability to recognize obstacles and traffic signs in real time by using deep neural networks. For 3D mapping and configured environment navigation, a simulation platform using the Pioneer 3-DX robot was developed. Cloud computing improves system scalability and offloads processing. Intelligent and versatile AGVs for urban and industrial applications are guaranteed by the suggested structure.
Ce travail intègre la vision par ordinateur basée sur le cloud et l’apprentissage profond afin d’améliorer la navigation des véhicules guidés autonomes (AGV). Il permet de reconnaître en temps réel les obstacles et les panneaux de signalisation en utilisant des réseaux neuronaux profonds. Afin de réaliser la cartographie en 3D et la navigation dans un environnement configuré, une plateforme de simulation utilisant le robot Pioneer 3-DX a été développée. Le cloud computing améliore la scalabilité du système et réduit le traitement. La structure proposée garantit des AGV intelligents et polyvalents pour des applications urbaines et indust
Keywords: AGV; 3D mapping; navigation; deep learning; computer visio